"Novas" legitimidades de segmentação do mercado de trabalho de jovens diplomados - Ana Paula Marques (Universidade do Minho, 2009)
Today as before, the dialectics of work and employment expresses profound contrasts. In this context, employability - understood as the probability both of accessing and staying in the labour market - plays with multiple aspects, which are not only linked with the individual and professional qualifications of those who look for a job, but also assume collective and unequal dimensions. The latter refers namely to the local inflexions of the macro-economical context within which the search for a job takes place, the human resource management strategies that companies resort to, and higher education as well as employment and training policies. In this article, based on the main results of diagnoses focusing on graduates and human resource managers, we will highlight the effects of the flexibility strategies adopted by companies considering the following dimensions: productive, training, functional, compensation, work schedule and type of contract. The "new" legitimacies that section these young executives are growingly based on the non-regulation of work relations and of the entrepreneurship policies adopted by most companies, exposing to a growing precariousness social groups that have invested on professional and academic formation, particularly in higher education. As a result, youngsters are confronted with the challenge of acepting uncertainty and using it as a real asset for action, that is, of gaining a certain identity (in)stability that may provide a sense of plausible biographic temporality. This includes internalising a culture of entrepreneurship and creative initiative resting on a high degree of transferability of the value of academic qualifications and of competencies and cultural orientations of superior technical-scientific training.